The role of dual filial piety as mediators in the relationship between parenting styles and filial piety behaviour of Malaysian - Lee, Chew Yee; Phang, Yong Nie (2020)
There was an increase of elderly abandoned cases caused by diminishing of filial piety behaviour in Malaysia. Perceived parenting styles and filial piety beliefs were reported as the factors that lead to declining of filial piety behaviour. Hence, this study aimed to examine the role of dual filial piety beliefs piety beliefs as mediators in the relation between perceived parenting styles of both parents and the filial piety behaviour among undergraduates in Malaysia. The questionnaires were distributed to 385 undergraduates from different institutions with the mean age of 21.25 (SD = 1.48), including 107 males and 278 females. Purposive sampling was used and the statistical technique used was multiple linear regressions through PROCESS Macro. The result showed that the regression model was statistically significant, F (6, 363) = 75.997, p < .001, and accounted for 55.7% of variance. It was found that authoritative fathering (ß = .098, p = .009), authoritative mothering (ß = .16, p = .003), RFP (ß = .39, p < .001) and AFP (ß = .37, p < .001) were found to predict filial piety behaviour. Meanwhile, authoritarian fathering (ß = -.02, p > .05) and authoritarian mothering (ß = -.10, p > .05) were not indicated as predictors of filial piety behaviour. Also, the findings have determined the significant mediating role of dual filial piety beliefs piety beliefs in the relation of perceived parenting styles and filial piety behaviour. This study may serve as a contribution to current literature as limited to no research on this topic was investigated in Malaysia. Also, parents can perform appropriate parenting style to nurture filial children while the policy maker can also make advancement in terms of elderly-support law to ensure adult children can pay the responsibility to take care of older parents and reduce the burden of country in handling neglected elderlies as well as cultivate the belief of filial piety in society.